Wyjść poza wyobrażony koncept natury. Rzecz o Piachu Urszuli Zajączkowskiej - Katarzyna Koza (Zagadnienia Rodzajów Literackich)
The starting point of this article is an attempt to prove the authenticity of the essential catchword of Julia Fiedorczuk’s ecocriticis, that “with the environmental crisis comes a crisis of the imagination” (citation from Lawrence Buell). In this article, the concept of disaster functions in an ecocritical practice is analysed and how we can avert anthropocentric and deleterious ways of thinking. An important context here is Timothy Morton’s concept of ecomimesis texts and more ecological, ambient poetics, where text reflects real processes which depart from the concept of imaginary nature. Specifically, this paper proves that in the latest poetry volume written by Urszula Zajączkowska, using the example of the volume Piach (2020), that firstly, the anthropocentric view of nature (which underlines the concept of ecomimesis) is abandoned, which, the imagined and servant, is far removed from the actual processes existing in the world. Secondly, the analysis and interpretation of selected texts in the poems confirms that the poetry exhibits a special sensitivity to changes and processes. In turn, this enables us to comprehend the effects of human actions. For this reason, the reader can exercise and practice his imagination, which is helped by the auratic poetics used. These activities facilitate a better understanding of the effects of human activities. Urszula Zajączkowska poetry’s prompts us to imagine how the materiality of the world works in practise and how these tiny atoms created the whole world. Also, this poetry fosters a way of thinking that assumes particular significance in the context of ongoing climate change, without necessarily aspiring for the currently popular apocalyptic themes.